The nuclear envelope and its involvement in cellular stress responses. - Malhas, A; Vaux, D (Biochemical Society, 2011)
The nuclear envelope is not only important for the structural integrity of the nucleus, but also involved in a number of cellular functions. It has been shown to be important for maintaining and controlling chromatin organization, sequestering transcription factors, replication, transcription and signalling. The nuclear envelope is thus important for development and differentiation, and some of its components are essential for cell viability. Among the many functions which are emerging for the nuclear envelope is its involvement in protecting the cell against different types of cellular stress. In the present paper, we review key findings which describe the roles of nuclear envelope components in responses to common types of stress conditions.